The new gamma interferon (IFN-γ) algorithm for tuberculosis diagnosis in cynomolgus macaques - Warit, Saradee; Meesawat, Suthirote; Cheawchanlertfa, Pattsarun; Makhao, Nampueng; Srilohasin, Prapaporn; Kaewparuehaschai, Machamon; Noradechanon, Kirana; Pomcoke, Areeya; Kemthong, Taratorn; Prammananan, Therdsak; Kanitpun, Reka; Palaga, Tanapat; et al. (PloS one, 2024)
Tuberculosis (TB) is the first infectious disease to be screened-out from specified pathogen-free cynomolgus macaques ( Macaca fascicularis ; Mf) using in human pharmaceutical testing. Being in either latent or active stage after exposure to the Mycobacterium tuberculosis complex (MTBC), the monkey gamma-interferon release assay (mIGRA) was previously introduced for early TB detection. However, a notable incidence of indeterminate results was observed. In this study, we compared two positive mitogen references, phytohemagglutinin (PHA) that is used in the QuantiFERON-TB Gold Plus kit (QFT-PHA) and a combination of Concanavalin A and Pokeweed mitogen (ConA+PWM), in a cohort of 316 MTBC-exposed Mf. Following a 29-month follow-up of 100 selected animals, we established a new mIGRA interpretation algorithm that demonstrated a significant shift in the negative and indeterminate cases regardless of whether the QFT-PHA or ConA+PWM was used as a mitogen. That is, if the OD NIL value was ≤0.18, OD MIT-NIL > OD NIL , and the OD TB1/2-NIL were ≥0.05 and ≥25% of individual OD NIL , the mIGRA result was interpreted as ‘positive’. If the OD NIL value was ≤0.18, OD MIT-NIL > OD NIL , and the OD TB-NIL was <0.05, the mIGRA result was interpreted as ‘negative’. If the OD NIL value was >0.18 or the OD of mitogen references [OD (QFT-PHA) and OD (ConA+PWM) ] were ≤0.18, the mIGRA result was interpreted as ‘indeterminate’. As a result, negative cases increased by 10–50%, indeterminate cases decreased by 40–80%, and the number of TB-positive cases remained unchanged. Our findings highlight the critical role of mitogens as positive controls in mIGRA interpretation. This study provides the mIGRA value for the TB screening of cynomolgus macaques that enables the identification of true positive and suspicious TB cases for quarantine programs.